2012
DOI: 10.1016/j.virol.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 IFN-independent activation of a subset of interferon stimulated genes in West Nile virus Eg101-infected mouse cells

Abstract: Although infection of mouse embryofibroblasts (MEFs) with WNV Eg101 induced interferon (IFN) beta production and STAT1 and STAT2 phosphorylation, these transcription factors (TFs) were not detected in the nucleus or on the promoters of four IRF-3-independent interferon stimulated genes (ISGs): Oas1a and Irf7 (previously characterized as IFN/ISGF3-dependent), Oas1b and Irf1. These ISGs were upregulated in WNV Eg101-infected STAT1−/−, STAT2−/−, and IFN alpha/beta receptor −/− MEFs. Although either IRF-3 or IRF-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 73 publications
4
35
1
Order By: Relevance
“…3). As previously reported, STAT2 was located in the cytoplasm in cells infected with Eg101 at 8, 12, and 16 h after infection (18). In contrast, some STAT2 was observed both in the cytoplasm and nucleus in some cells infected with W956IC at 8 h after infection (Fig.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…3). As previously reported, STAT2 was located in the cytoplasm in cells infected with Eg101 at 8, 12, and 16 h after infection (18). In contrast, some STAT2 was observed both in the cytoplasm and nucleus in some cells infected with W956IC at 8 h after infection (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Since a number of known and yet to be identified IPS-1 downstream molecules are expected to cross talk in mediating the signal to IFN-␤ and ISGs, further studies are needed to fully elucidate the mechanisms of induction of the antiviral state in WNV-infected cells. The results of a recent study from our lab showed that the initial upregulation of a set of ISGs in MEFs infected with the natural WNV strain Eg101 was only partially dependent on IPS-1 and that upregulation of these ISGs was independent of IFN-␤ both at early and late times of infection (18). The present study revealed a role for IPS-1 in mediating NF-B activation and IFN-␤ induction in cells infected with W956IC virus.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations